A Discourse on the Malay Cultural Identity within the Malaysian Society - Khalidah Khalid Ali (Kajian Malaysia, 2022)
The Malays are the main ethnic group of Malaysia, representing 50.4% of the total population and 63.1% of the population distribution in Peninsular Malaysia. They are among the identified bumiputera, together with the Orang Asli in Peninsular Malaysia and indigenous groups in Sarawak and Sabah. This discourse study relates to the cultural identity of the Malays and investigates their ethics and values from social constructionist approaches. Cultural identity includes the cultural background, religion/spirituality and socialisation. This research concurs with other studies that the Malay culture was characterised by a mix of animism, Hinduism and Buddhism, although the Malays have been identified with Islam as their religion. There are still remnants of animistic and Hinduistic beliefs and practices in the Malay Muslim life, especially in the practice of adat. While adat is a cultural and legally-defined element of the Malays in identity, the foundation of Malay ethics and value system is budi-Islam, adab and akhlak.